Study on the relationship between permeability coefficient and porosity, the confining and osmotic pressure of attapulgite-modified loess - Zhengrui Zhang; Ahad Amini Pishro; Lili Zhang; Xuejiao Ma; Siti Jahara Matlan; NazaruddinAbdulTaha; MojdehAmini Pishro (Springer Nature, 2023)
This study investigated attapulgite-modifed loess as an efcient and cost-efective method for creating an impermeable liner for landflls in regions with scarce clay resources. Laboratory permeability tests were conducted using a fexible wall permeameter to determine the permeability of compacted loess and attapulgite mixtures under varying osmotic conditions. The relationship between the permeability coefcient, attapulgite dosage, radial pressure, and osmotic pressure was analyzed. Nuclear magnetic resonance and scanning electron microscopy were also used to observe the microstructure of the modifed loess. The results showed that attapulgite dosage signifcantly reduced the permeability coefcient, but the efect became limited when the content surpassed 10%. The decrease of the permeability coefcient of the modifed loess is mainly due to the flling of pores between the loess by attapulgite, which makes the pore size and throat size of the modifed loess smaller. The modifed loess displayed a sheet structure that contributed to an increased permeability coefcient due to increased radial pressure. This study provides valuable insights into using attapulgite-modifed loess as a material for landfll lining in regions with scarce clay resources.